The midwife murders - Patterson, James, 1947-; DiLallo, Richard (Grand Central Publishing, 2020)
When two kidnappings and a stabbing occur on her watch in a Manhattan university hospital, a fearless senior midwife teams up with a skeptical NYPD detective to investigate rumors that shift from the Russian Mafia to an underground adoption network.